2020
DOI: 10.1038/s41598-020-68718-4
|View full text |Cite
|
Sign up to set email alerts
|

Human milk and mucosa-associated disaccharides impact on cultured infant fecal microbiota

Abstract: Human milk oligosaccharides (HMOs) are a mixture of structurally diverse carbohydrates that contribute to shape a healthy gut microbiota composition. The great diversity of the HMOs structures does not allow the attribution of specific prebiotic characteristics to single milk oligosaccharides. We analyze here the utilization of four disaccharides, lacto- N -biose (LNB), galacto- N -biose (GNB), fucosyl-α1,3-GlcNAc (3FN) and fucosyl-α1,6-GlcNAc (6FN), that form part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“… 43 Using in vitro fermentation analysis, our group and others have demonstrated that LNB is metabolized by infant-gut associated bifidobacteria. 24 , 27 Here, this disaccharide is tested for the first time using an in vivo model and it has been demonstrated that it significantly increased the relative abundance of the genus Bifidobacterium in feces. However, the absolute levels of this genus in the LNB mice group were similar to the control group (Supplemental Figure 3 ), suggesting that the high relative abundance of Bifidobacterium in LNB could be due to reductions in the relative abundances of other taxa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 43 Using in vitro fermentation analysis, our group and others have demonstrated that LNB is metabolized by infant-gut associated bifidobacteria. 24 , 27 Here, this disaccharide is tested for the first time using an in vivo model and it has been demonstrated that it significantly increased the relative abundance of the genus Bifidobacterium in feces. However, the absolute levels of this genus in the LNB mice group were similar to the control group (Supplemental Figure 3 ), suggesting that the high relative abundance of Bifidobacterium in LNB could be due to reductions in the relative abundances of other taxa.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Indeed, a B. longum strain isolated from fermented cultures with infant gut microbiota was able to grow in the presence of GNB. 24 The positive effect of LNB, GNB or 6FN in the persistence of B. longum species in the gastrointestinal tract is a relevant outcome, since this bacterium has been widely associated with prevention and fighting of several intestinal and immune diseases. 45 , 46 Regarding B. adolescentis species, it has been shown previously that this species is not able to metabolize 3FN and 6FN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, this differs from the consistent anti-adhesive effects observed in the present study, which utilized purified HMOs rather than whole milk. Thus, despite the recent progress in the study of the individual HMO components and their influence on bacterial growth (e.g., [45]), additional research is required to clarify their collective influence on functional probiotic characteristics such as bacterial adhesion ability.…”
Section: Discussionmentioning
confidence: 99%